2016
DOI: 10.3390/su8040311
|View full text |Cite
|
Sign up to set email alerts
|

School Facilities and Sustainability-Related Concepts: A Study of Hellenic Secondary School Principals’, Teachers’, Pupils’ and Parents’ Responses

Abstract: Effective building environment sustainability frameworks and practices need to take users' opinions into account. For this purpose, a survey questionnaire was developed and the "Panhellenic survey of school spaces, materials and environmental-comfort conditions in secondary schools and perceptions, stances and attitudes of pupils, teachers, principals and parents towards sustainable construction and the selection and use of materials in schools that are friendly to the environment and human health" was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Furthermore, the visual disconnection between unsustainable buildings and poor investment was associated with conflating and delegitimizing the potential power of ecological learning around health and sustainability (Chapman, 2012*;Dolan, Sturm, & Wollmuth, 2006*;Zepatou, Loizidou, Chaloulakou, & Spyrellis, 2016*).…”
Section: Indoormentioning
confidence: 99%
“…Furthermore, the visual disconnection between unsustainable buildings and poor investment was associated with conflating and delegitimizing the potential power of ecological learning around health and sustainability (Chapman, 2012*;Dolan, Sturm, & Wollmuth, 2006*;Zepatou, Loizidou, Chaloulakou, & Spyrellis, 2016*).…”
Section: Indoormentioning
confidence: 99%
“…Users' opinions must be considered ineffective in building environmental sustainability frameworks and practices. To progress toward sustainable buildings, it has been suggested that objective and unbiased criteria for users' impressions of existing buildings be devised and incorporated into appropriate building sustainability grading methods (Zepatou et al, 2016).…”
Section: School Facilitiesmentioning
confidence: 99%
“…A checklist was used to examine the building condition, student-teacher ratio, dropoutrate, and missing facilities. It was finalized after studying the checklist used by Zepatou et al (2016), and also consultation with the working teachers.…”
Section: Design and Instrumentsmentioning
confidence: 99%